Non-immunization associated with increased risk of sudden unexpected death in infancy: A national case–control study. Issue 2 (9th January 2023) - Deschanvres, Colin; Levieux, Karine; Launay, Elise; Huby, Anne-Cécile; Scherdel, Pauline; de Visme, Sophie; Hanf, Matthieu; Gras-Le Guen, Christèle; ,
Highlights: Non-immunization was significantly associated with increased risk of SUDI. The immunization schedule analyzed contained the combined hexavalent vaccine. The immunization schedule analyzed contained the conjugated pneumococcal vaccine. Abstract: Objective: In the context of vaccine scepticism, our study aimed to analyse the association between immunization status and the occurrence of sudden unexpected death in infancy (SUDI). Study design: A multi-centre case–control study was conducted between May 2015 and June 2017 with data from the French national SUDI registry ( OMIN ) for 35 French regional SUDI centres. Cases were infants under age 1 year who died from SUDI and who were registered in OMIN. Controls, matched to cases by age and sex at a 2:1 ratio, were infants admitted to Nantes University Hospital. All immunization data for diphtheria (D), tetanus (T), acellular pertussis (aP), inactivated poliovirus (IPV), Haemophilus influenzae b (Hib), hepatitis B (HB) and 13-valent pneumococcal conjugate vaccine (PCV13) were collected by a physician. Cases and controls were considered immunized if at least one dose of vaccine was administered. Results: A total of 91 cases and 182 controls were included. The median age was 131 days (interquartile range 98–200.0) and the sex ratio (M/F) was about 1.1. For all vaccines combined (D- T -aP-IPV-Hib and PCV13), 22 % of SUDI cases versus 12 % of controls were non-immunized, which was significantly associated with SUDI after adjustment for potential adjustment factors (adjusted odds ratio 2.01 [95 % confidence interval 1.01–3.98, p = 0, 047]). Conclusions: Non-immunization for D- T -aP-IPV-Hib-HB and PCV13 was associated with increased risk of SUDI. This result can be used to inform the general public and health professionals about this risk of SUDI in case of vaccine hesitancy.